Réécriture parodique dans un road novel de Peter Handke - Jenny Brasebin (Recherches Germaniques)
Peter Handke’s In einer dunklen Nacht ging ich aus meinem stillen Haus challenges how wandering has been traditionally thematized in literature. It belongs to a particular genre, the road novel, which emerged in the post-war western world, undoubtedly influenced by the seminal work of Jack Kerouac. Interestingly, Handke’s novel, published in 1997, is closely related to a story written eight centuries prior : Yvain ou le chevalier au lion by Chrétien de Troyes. Not only are there numerous direct or indirect allusions to the medieval book, the plot itself revolves almost entirely around the canons of the chivalry novel, which Handke reproduces while simultaneously reorienting them from their original meaning. We could therefore consider that the Austrian writer’s piece constitutes a sort of parodic rewriting of Chrétien de Troyes’ text, and that it is precisely this tribute and transformation process which could define it as a road novel.